2009
DOI: 10.1002/da.20504
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of anxiety and depression on interoceptive accuracy

Abstract: Our results highlight the possible relationship between depressive symptoms and interoceptive awareness and may have further implications for theoretical models of anxiety disorders and their treatment. Further research is required to examine the potential consequences of altering interoceptive awareness in healthy subjects in relation to depression and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
187
5
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(214 citation statements)
references
References 61 publications
19
187
5
3
Order By: Relevance
“…Depression seemed to have differential effects on perspiration perception, strongly attenuating IAc in comorbidity with panic, but having even a small incremental effect on IAc of no-panic-controls. With this result we were aligned with recent findings (Pollatos et al, 2009;Dunn et al, 2007Dunn et al, , 2010 about possible interoception-enhancing effects of depression, although we could not show this effect in heart-rate perception (see Fig. 3a).…”
Section: Interoceptive Accuracy Conclusionsupporting
confidence: 90%
See 2 more Smart Citations
“…Depression seemed to have differential effects on perspiration perception, strongly attenuating IAc in comorbidity with panic, but having even a small incremental effect on IAc of no-panic-controls. With this result we were aligned with recent findings (Pollatos et al, 2009;Dunn et al, 2007Dunn et al, , 2010 about possible interoception-enhancing effects of depression, although we could not show this effect in heart-rate perception (see Fig. 3a).…”
Section: Interoceptive Accuracy Conclusionsupporting
confidence: 90%
“…Current papers report differential effects. Comorbidity of anxiety and depression seemed to decrease HR-IAc, whereas anxiety alone (and by trend even depression alone) were associated with an increase of IAc (Pollatos et al, 2009;Dunn et al, 2010). Subjects with higher levels of depression had better IAc than those with lower levels (Dunn et al, 2007).…”
Section: Heart-rate Interoceptive Accuracy In Panic and Comorbid Deprmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent research has suggested that an association exists between a person's sensitivity to their own heartbeat and the intensity of emotion they experience (Herbert et al, 2007;Pollatos et al, 2007b;Wiens et al, 2000). Furthermore, a number of studies have reported that measures of the accuracy of heartbeat perception positively correlate with measures of affective traits, such as tendencies for general anxiety (Pollatos et al, 2007a(Pollatos et al, , 2009Stewart et al, 2001). These empirical studies support the notion that the central monitoring and representation of bodily signals play a fundamental role in emotion.…”
Section: Introductionmentioning
confidence: 57%
“…Minimally, the increased weighting of interoceptive signal may increase interoceptive accuracy, decreasing the impact of dysfunctional simulations and selfrepresentations on cognitive and behavior, as previously proposed (Farb et al, 2012a). For example, depression is characterized by external locus of control, learned helplessness, and low self-efficacy, and some evidence suggests depressed people have poorer interoceptive accuracy (Ehlers and Breuer, 1992;Pessoa and Ungerleider, 2004;Dunn et al, 2007;Pollatos et al, 2009), whereas mindfulness training appears to bolster self-efficacy (Chang et al, 2004). Furthermore, mindfulness training has been associated with normalization of the gait pattern of depressed individuals, suggesting concurrent changes in proprioceptive and emotional responses (Michalak et al, 2011).…”
Section: Enhanced Presence and Agencymentioning
confidence: 81%